Diagnosis of Peritoneal Metastases with Abdominal Malignancies: Role of ADC Measurement on Diffusion Weighted MRI - Onur, Mehmet Ruhi; Akyol, Muammer; Poyraz, Ahmet Kursad; Kocakoc, Ercan; Ogur, Erkin (Aves, 2012)
Objective: The purpose of our study was to evaluate the utility of the apparent diffusion coefficient (ADC) value measurement in the diagnosis of peritoneal metastases on diffusion weighted magnetic resonance imaging. Materials and Methods: Diffusion weighted imaging with conventional magnetic resonance imaging sequences was performed on twenty consecutive oncology patients (group I) with peritoneal metastases. The ADC values of the metastases, the peritoneal fat around the metastases (group I) and the peritoneal fat in patients with no malignancy (group II) at b(0-100), b(0-600), and (b 0-1000) s/mm(2)gradients were measured and compared. Results: The apparent diffusion coefficient values of three gradients in peritoneal metastases (2.27 +/- 0.4; 1.67 +/- 0.7 and 1.09 +/- 0.4x10(-3) mm(2)/s at b 100, 600 and 1000 gradients, respectively) were significantly lower than the ADC values of the peritoneal fat around metastases (3.07 +/- 0.4; 2.07 +/- 0.4; 1.33 +/- 0.3x10 (3) mm(2)/s at b 100, 600 and 1000 gradients, respectively) (p<0.05). There was no significant difference between the ADC values of peritoneal fat in the patients of group I and group II at the 3 diffusion gradients (p>0.05). Conclusion: The measurement of ADC values may be used as a complementary diagnostic method in differentiating peritoneal metastases from peritoneal fat on Diffusion Weighted MRI (DWMRI DWMRI).
Abdominal malignansilerin peritoneal metastazlarının tanısında difüzyon a?ırlıklı MRG'de görünür difüzyon katsayısı ölçümünün rolü
Keywords: Apparent diffusion coefficient value; Diffusion weighted imaging; Malignancy; Metastasis; Peritoneum